Pengaruh Risiko Kredit, Risiko Likuiditas, dan Efisiensi Operasional terhadap Kinerja Keuangan : (Pada Sektor Perbankan Konvensional yang Terdaftar di Bursa Efek Indonesia Periode 2019-20230 - Ika Meilia; Ahmad Idris; Dadang Afrianto (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to determine the effect of Credit Risk, Liquidity Risk, and Operational Efficiency on Financial Performance in the Conventional Banking Sector listed on the Indonesia Stock Exchange for the period 2019-2023. The research method used is quantitative using secondary data obtained from the Indonesia Stock Exchange, namely the annual financial reports of conventional banks. The sampling technique was carried out using the purposive sampling method. The analysis was carried out with credit risk using the Net Performing Loan (NPL) ratio, liquidity risk using the Loan to Deposits Ratio (LDR) ratio, operational efficiency using the Operating Expenses to Operating Income (BOPO) ratio and financial performance was measured using Return On Assets (ROA). The results of the study showed that partially the credit risk variable had a significant negative effect on financial performance, liquidity risk did not have a significant effect on financial performance, operational efficiency did not have a significant effect on financial performance. Simultaneously, credit risk, liquidity risk, operational efficiency had a significant effect on financial performance.